Transureteral Lithotripsy of Ureteral Calculi in Children with Holmium: Yttrium Aluminium Garnet Laser - Amjadi, Mohsen; Kazemi Rashed, Fahimeh; Sari Motlagh, Reza; Sheikh Monazzah, Farzin (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: Surgical management of pediatric urinary calculi evolved dramatically over the past two decades. However, with the miniaturization of equipment and with improvisation of endourologic techniques, access to the entire pediatric urinary system is possible. Ho: YAG laser provides more maneuverability during transuretereal lithotripsy (TUL) than the pneumatic system which uses a metal probe, especially when used in pediatrics urinary systems. In this study, we report our experience about treatment of pediatric ureteral stone with HO: YAG laser. METHODS: Between 2008 -2011, 41 children ≤ 12 years of age with ureteral stones were included in our study. Using K.U.B, sonography, and intravenous urogram, diagnoses were established for all patients. 6F or 8F wolf semi rigid ureteroscope was used for ureteroscopy under general anesthesia and stone fragmentation was implemented by Ho: YAG laser. For the evaluation of stone free rate, we used the following day & week confirmatory KUB, and sonograms additional to the direct visualization of the ureter during ureteroscopy. The patients were scheduled to be followed by control sonograms 2 weeks and 2 months after the operation to rule out past operational ureteral stenosis. RESULTS: From our 40 patients whose ages were in the range of 8 months and twelve years of old with a mean age 3.5 years, 18 patients (45%) had distal ureteral stones, ten (25%) in mid ureter, and twelve of them (30%) had the stone in their proximal ureter. The mean diameter of stones was 9.3 mm (3.5-11 mm). Three patients had encrusted double j stents (DJS). Our overall stone free rate was 89.35% at the end of 1 week. The complications were fever in 5 patients (12.5%) and ureteral stricture due to ureteral perforation in one patient, while one patient had long hospital stay due to refractory pain and nausea. The mean time of post-surgical hospital stay was 42 hours, while for only 20% of patients (8 patients) and in the rest of patients (30 patients) this period was only 24hours. DISCUSSION: Endoscopic lithotripsy in children has gradually become a major technique for the treatment of ureteral stones. This progression has been on the basis of the development of appropriate endoscopes and effective working instruments. The stone-free rate following urteroscopic lithotripsy for ureteral stones has been reported in as high as 98.5-100%. In this study, overall stone free rate was 89.35%. The complications after ureteroscopic laser lithotripsy are uncommon and usually related to passage of the ureteroscope than from laser action. Fever was the most common complication which occurred in 5 (12.5%) of our patients despite the fact that all patients were hospitalized the day before the procedure and were under parenteral antibiotic therapy. Postoperative stenting after ureteroscopic lithotripsy remained controversial. Most children were able to tolerate the attached string and the stent could be removed 5-7 days after without the use of an additional anesthetic. We used suitable ureteral catheters for 24 hours in all patients. CONCLUSION: Although HO: YAG laser lithotripsy is safe in children, we need more controlledtrials to show the best method of lithotripsy in pediatric ureteral stones.